2022
DOI: 10.7554/elife.81071
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic burst reactivation of hippocampal neurons enables associative plasticity of temporally discontiguous inputs

Abstract: A fundamental unresolved problem in neuroscience is how the brain associates in memory events that are separated in time. Here we propose that reactivation-induced synaptic plasticity can solve this problem. Previously, we reported that the reinforcement signal dopamine converts hippocampal spike timing-dependent depression into potentiation during continued synaptic activity (Brzosko et al., 2015). Here, we report that postsynaptic bursts in the presence of dopamine produce input-specific LTP in mouse hippoca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Consistent with our previous results that burst-induced potentiation in the presence of dopamine requires postsynaptic PKA and protein synthesis (Fuchsberger et al, 2022), we found here that synaptic potentiation induced by low frequency synaptic stimulation in the presence of dopamine following a priming protocol, which would otherwise induce synaptic depression (Brzosko et al, 2015), also requires postsynaptic PKA and new protein synthesis. While conventional t-LTP remained intact, blocking protein synthesis in the postsynaptic neurons completely prevented DA-LTP, suggesting that dopamine induces the synthesis of plasticity-related proteins required for converting synaptic depression into potentiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous results that burst-induced potentiation in the presence of dopamine requires postsynaptic PKA and protein synthesis (Fuchsberger et al, 2022), we found here that synaptic potentiation induced by low frequency synaptic stimulation in the presence of dopamine following a priming protocol, which would otherwise induce synaptic depression (Brzosko et al, 2015), also requires postsynaptic PKA and new protein synthesis. While conventional t-LTP remained intact, blocking protein synthesis in the postsynaptic neurons completely prevented DA-LTP, suggesting that dopamine induces the synthesis of plasticity-related proteins required for converting synaptic depression into potentiation.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently reported that, in addition to synaptic activation, postsynaptic burst stimulation can also induce DA-LTP, which is mediated via the same AC-PKA signalling pathway and also requires protein synthesis (Fuchsberger et al, 2022). Synaptically induced DA-LTP develops gradually, while burst-induced DA-LTP shows rapid potentiation.…”
Section: Da-ltp Requires Cp-amparsmentioning
confidence: 99%
“…It shows that 1) BTSP drives the dynamics of hippocampal representations during familiarization, 2) the average probability of BTSP-triggering events is higher during novel experiences than familiar ones, especially in CA1, and the shape of the BTSP rule changes with familiarity in CA3. Novelty-dependent neuromodulatory and inhibitory signals (Pedrosa & Clopath, 2020; Sheffield et al, 2017) could mediate these changes by modulating both synaptic eligibility traces and the probability and duration of BTSP-triggering calcium plateaus (Fuchsberger et al, 2022; Magee & Grienberger, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 30, 2023. ; https://doi.org/10.1101/2023.06.29.547097 doi: bioRxiv preprint input 12,13,59 and; 2) BTSP, where the pairing of temporally discontiguous pre-and postsynaptic activation induces synaptic potentiation 17 . In the former case, the genesis of eligibility traces per se is conjunctive in nature since it relies on both pre-and postsynaptic events, a hallmark of STDP protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Protracted eligibility traces would thereby allow individual neurons to solve the temporal credit assignment problem by binding cues that are separated by behaviorally relevant temporal delays. An emerging literature is beginning to identify forms of synaptic plasticity that exhibit temporal features that are consistent with the existence of a neural correlate of eligibility traces 12,13,14,15,16,10 . In particular, important recent work in the hippocampus has outlined the presence of a novel form of synaptic plasticity, termed Behavioral Timescales Synaptic Plasticity (BTSP), that emerges following the pairing of synaptic and cellular events that are separated by up to ~ 2 seconds 17,18,19 .…”
Section: Mainmentioning
confidence: 99%